IMPLEMENTASI LIVING HADIS DALAM PELAKSANAAN SHALAT DHUHA: STUDI KASUS PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN DARUL HIKMAH MATARAM - nida, sofwatun; Hidayat, Yusron; Krismonadi, Fani; Mandar, Yasri; Hidayah, Ahwil Lutan (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
The purpose of this study was to analyze the genealogy of thought and the process of forming the Dhuha Prayer tradition in the Islamic boarding school, identify supporting and inhibiting factors for its implementation, and reveal the advantages obtained by students from this routine practice. This study uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews with educators, participatory observation, and documentation studies. Data analysis techniques were carried out through the stages of reduction, presentation, and drawing conclusions systematically. The results of the study indicate that the implementation of the Dhuha Prayer at the Darul Hikmah Islamic Boarding School in Mataram has been institutionalized as a sustainable religious culture. This tradition is led by the caretaker of the Islamic boarding school as an authoritative figure who transmits Islamic values ??through a living hadith approach. Supported by the Islamic boarding school norm system, internal motivation of students, and supporting facilities, this practice has proven effective in shaping the religious character of students. Obstacles remain, such as environmental influences and low awareness of some students, but do not hinder the essence of spiritual transformation achieved through the habituation of this worship.